Coarse Grained Molecular Dynamic Simulations for the Study of TNF Receptor Family Members' Transmembrane Organization - Sica, Mauricio P.; Smulski, Cristian R. (Frontiers in Cell and Developmental Biology, 2021)
The TNF superfamily is composed by 19 ligands and 30 receptors. The oligomeric properties of ligands, both membrane bound and soluble, has been largely studied. However, less is known about the oligomeric properties of TNF receptors. Initial reports identified the extracellular, membrane-distal, cysteine-rich domain as a pre-ligand assembly domain. This region mediates stabilization of receptor dimers and/or trimers in the absence of ligand. Nevertheless, recent reports highlight the intrinsic role of the transmembrane domains to form dimers (p75NTR), trimers (Fas) or dimers of trimers (DR5). These studies were based on structural NMR which is complex, expensive and may be difficult to implement depending on the amino acid composition of the receptor. Here we report an unbiased in silico molecular dynamics approach using coarse grained models with Martini force field to study transmembrane homotypic interactions. We have tested the three known NMR transmembrane structures in simulated membrane patches composed by 36 helices of the same receptor equidistantly distributed. Our results strongly resemble the structural NMR findings both in oligomeric structure and specific residues involved in homotypic interactions, supporting the validity of our approach. This method will allow for more complex experimental setups to study different transmembrane segments, pathogenic mutations located in this region, different lipid environments as well as associations with other integral membrane proteins.